Help-Seeking Latina Victims of Domestic Violence and the Programs That Serve Them in New York City - Ortiz-Rodriguez, Yolanda (2016)
Domestic violence has impacted, and continues to impact the lives of many women. Although impacted by domestic violence, all women may not experience domestic violence in the same way. The purpose of this research was to explore differences that may exist between help-seeking foreign-born Latina and help-seeking U.S-born Latina victims of domestic violence. Using a purposeful sample of 32 help-seeking Latinas who were actively receiving services in one of the many domestic violence programs in New York City, the researcher set out to explore differences in use of services, experiences with domestic violence, perceptions of domestic violence, and satisfaction with program services. Feminist standpoint theory was used as the conceptual framework and intersectionality theory as a lens to facilitate the identification of differences that may exist between the study groups. The results of this study include consequences associated with help-seeking, the need for improving the criminal justice response to domestic violence, and more importantly, the stated needs of help-seekers. In addition, coercive control, effects of domestic violence, the need for accessible and adequate services, and implications for future research are also discussed